DESIGN AND STRESS ANALYSIS OF VERTICAL RISER CLAMPED ON PLATFORM LEG - Axel
The pipeline is one of the most important components in the oil and gas industry. Therefore, a good design process of the riser is important to avoid failure. In this final project, there will be several riser wall thickness designs with three standards to compare, which is DNV-OS-F101, DNV-OS-F201, and ASME B31.8. Then, proceed with conducting a free span analysis with DNV 1981 to obtain the length of the allowable spans, due to both static and dynamic loads. The allowable span will be used to obtain all of the riser support position that is attached to the platform leg to support the riser. Moreover, the sacrificial anode will be designed for the riser, so that the corrosion of the riser can be avoided. Then, the thermal expansion analysis and expansion spool design are performed, which serves to prevent overstress on the riser. After the results are obtained, a stress analysis is performed on the designed riser. The design results show that the minimum wall thickness design with DNV-OSF201 is the thinnest, which is 9,9 mm, compared with 10 mm with DNV-OS-F101 and 11,1 mm with ASME B31.8. Of the three, choose a wall thickness which available in API 5L, which is 12,7 mm. From the free span analysis, the results of successive span length designs from the sea surface to the seabed are 6,7 m, 5,75 m, 6,25 m, 6,25 m, 6,25 m, 6,25 m, 6,6 m, and 6,6 m. Then from the thermal expansion analysis and expansion spool design, the pipeline will expand by 10,84 mm and will require a 7 m long expansion spool. The results of the stress analysis on CAESAR software obtained a maximum ratio of 37.8% under hydrotest conditions.